Development and Validation of Wisdom Scale for a Sample of University Students in Gaza - H. Tahoon, Hussein; M. Abu Ghali, Etaf; Ahmed Haiba, Mohamed; Suliman Mohammed Sheikh Aleed, Raeda (International Journal of Psychosocial Rehabilitation, 2020)
The present study attempts to examine the structure and examine psychometric properties of the wisdom scale for a sample of university students in Gaza . The study questions addressed are: What is the structure of the measure of wisdom for university students in Gaza? Does the wisdom scale have appropriate psychometric properties? A total of 170 students From Al-Quds Open University and Al-Aqsa University in Gaza, the scale of wisdom was completed, including males (N= 100) and females (N= 70). The students ranged in age from 18 to 22, with an average age of 20.7 and an S.D. of 2.1. Exploratory factor analysis (EFA) is used. The results indicate that the structure of wisdom is multidimensional, which includes emotional stability, psychological resilience, persuasion skills, and problem-solving skills. And the scale has appropriate psychometric properties.